Digital Financial Ecosystems: From Inclusive Digital Finance to Financial Capability (International Journal of Business Innovation, 2023)
This research involved 1080 private sector employees in Kumasi Metropolis of Ghana and employed econometrics analysis to investigate the influence of financial capability on digital financial inclusion. It utilized Sen's Capability Approach (CA) as an alternative framework and collected data between July 2021 and November 2022, subsequently transforming it into panel data. The study found that financial literacy, financial skills, financial behavior, and financial attitude collectively account for 75.4% of the variation in digital financial inclusion. Specifically, financial literacy increased digital financial inclusion by 0.029% at the 5% significance level, financial skills significantly boosted it by 2.289% at the 1% level, financial attitude contributed to a 1.419% improvement, and financial behavior led to a 0.915% increase. These findings underscore the vital roles played by financial literacy, skills, attitude, and behavior in promoting digital financial inclusion.
Keywords: Digital Financial Inclusion; Financial Capability; Financial Literacy; Financial Skills; Financial Behaviour; Financial Attitude